PENDAMPINGAN MOTIVASI BELAJAR MELALUI MEDIA GENIAL PASCA PANDEMI COVID PADA SISWA SMK MUHAMMADIYAH 2 WATES - Anita Dewi Astuti; Endah Rahmawati; Atika Dwi Evitasari; Siwi Utaminingtyas; Faridl Musyadad (Universitas Majalengka, 2022)
Abstract (Tahoma, 9pt Bold) The spread of the COVID-19 virus, which began to decline, caused the goverment to hold limited Face-to-face Learning (PTM) activities in several areas to fulfill children's learning rights. One of the problems faced in Limited Face to Face Learning (PTM) is that many students have low learning motivation as a result of the previous online learning implementation. The objectives of this mentoring program are (1) to determine the implementation of the mentoring program; (2) to find out the advantages and disadvantages of the genial media used in the mentoring program; (3) to find out the participants' responses regarding the genial media application; and (4) to find out the participants' responses to the mentoring program. The method applied by the servant as a supporter of success in the implementation of this mentoring is multi-method, namely lectures, questions and answers, demonstrations, and practice. The results obtained from this mentoring program can be concluded that the activities can run smoothly, getting a fairly good response in the use of genial media applications as well as positive responses from participants who take part in the mentoring program. Keywords: Learning Motivation; Genial Media; Post Covid Pandemic Abstrak Penyebaran virus covid 19 yang mulai menurun menyebabkan pemerintah menyelenggarakan kegiatan Pembelajaran Tatap Muka (PTM) terbatas di beberapa daerah guna memenuhi hak belajar anak. Salah satu permasalahan yang dihadapi pada Pembelajaran Tatap Muka (PTM) Terbatas adalah banyak siswa yang mempunyai motivasi belajar rendah hal ini sebagai dampak dari pelaksanaan pembelajaran sebelumnya yang diselenggarakan secara daring. Tujuan dari program pendampingan ini adalah (1) untuk mengetahui pelaksanaan program pendampingan; (2) untuk mengetahui kelebihan dan kekurangan dari media genial yang digunakan dalam program pendampingan; (3) untuk mengetahui tanggapan peserta terkait aplikasi media genial; dan (4) untuk mengetahui respon peserta terhadap program pendampingan. Metode yang diterapkan pengabdi sebagai penunjang keberhasilan dalam pelaksanaan pendampingan ini adalah multimetode, yaitu ceramah, tanya jawab, demonstrasi, dan praktik. Hasil yang diperoleh dari program pendampingan ini dapat disimpullkan bahwa kegiatan dapat berjalan lancar, mendapatkan respon yang cukup baik dalam penggunaan aplikasi media genial sekaligus respon yang positif pula dari peserta yang mengikuti program pendampingan. Kata Kunci: Motivasi Belajar; Media Genial; Pasca Pandemi Covid